Friction Stir Welding (FSW) process evaluation of aluminum Tie components used in the door mechanism of MAN trains (2021)
This project is focused in the development of a welding procedure using the Friction Stir Welding (FSW) process as an alternative for the local manufacture of components using lightweight materials without requiring great investment in specialized machinery. As case of study, a structural aluminum piece called “Tie” used in the railway cars owned by Metro de Medellín was selected and evaluated using analytical and computational tools to propose a viable alternative in accordance with the process, accessible materials and mechanical requirements. A prototype was successfully design and constructed according to the FSW proposed procedure, using the aluminum alloy AA6082 – T4 as base material, and after 5 months of operation and more than 1540 cycles, the tie does not present any problem or discontinuities which could jeopardize its mechanical performance; finally validating the possible usage of FSW as manufacturing alternative and giving a chart for future developments. The project was aligned with the results with a major plan called “Implementation of friction stir welding (FSW) in the Colombian rail transport sector” funded by the Royal Academy of Engineering and technically supported by TWI.